High temperature processes of phase formation in the system «cement «Gorkal-70» — microsilica» - Онасенко, Юлия Анатольевна; Песчанская, Виктория Викторовна (Technology audit and production reserves, 2013)
The use of microsilica in the refractory concrete on calcium aluminates cement contributes to the formation of an effective structure and physico-mechanical properties of concrete in linings of thermal units. The features of high-temperature processes in the system "calcium aluminates cement – microsilica", and the formation of the crystalline and amorphous phases are determined by the ratio of components, their mineralogical and chemical composition. The article presents the results of studies of the physical and chemical processes occurring during the thermal heating of model mixtures of hydrated compositions "cement« Gorkal-70 " – mcrosilica." Using the differential thermal analysis and X-ray diffraction, we have studied the effect of low quality microsilica on the mechanism of phase formation and established the mineralizing effect of impurities on the formation of the crystalline and amorphous phases. The article shows the possibility of directional control of the synthesis of anorthite and gehlenite by varying the proportion of the components of the system "cement« Gorkal-70 "- microsilica," which affects the formation of a given structure and properties of refractory concrete.